Comparison of the Effectiveness of Full Negative Pressure with Half Negative Pressure on Suction Drain in Reducing Post-Modified Radical Mastectomy Seroma - Gulraj Singh; Mulawan Umar; Nur Qodir (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2019)
Abstract Introduction: Modified radical mastectomy (MRM) is a breast cancer treatment option that is still operable. One of the postoperative complications that can be found is the formation of seroma. High negative suction drain is done to treat seroma after surgery but it can contribute to increase the length of stay in hospital. Methods: This study was a clinical randomized control trial (cRCT) conducted on 30 breast cancer patients in June - July 2019 at Moehammad Hoesin Hospital in Palembang. This study divided the two sample groups, each group consisting of 15 patients. One group was given half negative pressure on suction drain (experimental group) and the other used full negative pressure on suction drain (control group). Results: There was a significant difference (p <0.005) between the full and half negative pressure groups where there were more seroma events in the full vacuum group in 9 (60%) cases and half vacuum in 2 (30%) but there were no significant differences in long period of stay (p> 0.005). Conclusion: Half negative pressure is more effective in treating seroma than full negative pressure.